Preliminary study of supermarket's mobile application needs for Indonesian shopper / Shania Jiehan Geraldine and Dianing Ratri - Geraldine, Shania Jiehan; Ratri, Dianing (Universiti Teknologi MARA, Perak, 2022)
The increasing interest in smart city development provides an opportunity for retail to enter into what is known as the smart retail concept. Smart retail is a smart shopping concept with the help of technology. One of the technologies that can be used in the implementation of smart retail is smartphones. In Indonesia, large supermarkets such as Yogya and Super Indo have implementing smartphone technology, into them of mobile applications. However, based on the results of user reviews in the App store/Playstore media, the application is still considered not very effective. This is what makes researchers interested in evaluating mobile applications for supermarkets. The method used in this research is mixed method by conducting Focus Group Discussions and Questionnaires. The results of the data were analyzed with the aim of finding problems commonly experienced by visitors. There were 6 FGD participants and 137 questionnaire respondents included in this study. Based on the results, it is found that the current applications do not meet consumer needs, this is because consumers prefer to shop directly at the supermarket. However, in the process of in-store shopping activity, problems are still often found, such as difficulty in finding the location of the product, the product is unavailable, there is no information on the price of the product on display, and so on. Thus, the type of application that has the potential as a solution to this problem is an application to help visitors in doing in-store shopping activity at the supermarket.